The Games Gods Play (Standard Edition) - Owen, Abigail (Entangled: Red Tower Books, 2024)
"I have never been favored by the gods. Far from it, thanks to Zeus. Living as a cursed office clerk for the Order of Thieves, I just keep my head down and hope the capricious beings who rule from Olympus won't notice me. Not an easy feat, given San Francisco is Zeus' patron city, but I make do. Until the night I tangle with a different god--the worst god. Hades. For the first time ever, the ruthless, mercurial King of the Underworld has entered the Crucible--the deadly contest the gods hold to determine a new ruler to sit on the throne of Olympus. But instead of fighting their own battles, the gods name mortals to compete in their stead. So why in the Underworld did Hades choose me--a sarcastic nobody with a curse on her shoulders--as his champion? And why does my heart trip every time he says I'm his?"-- Provided by publisher.